Pengaruh Budaya Organisasi Terhadap Kinerja Tenaga Medis (Studi Kasus Bagian Keperawatan RS.Imanuel Bandar Lampung) - Wahyu Krisstyaningrum; Hesti Widi Astuti (Universitas Malahayati, 2016)
This study aims to determine the influence of organizational culture on the performance ofmedical personnel Immanuel Hospital Bandar Lampung , that can be obtained about the experience ofthe real problems faced by Immanuel Hospital and can be used as consideration to overcome theproblems encountered and efforts to achieve the goals by Immanuel Hospital. In this study, dataanalysis tool used is validity, reliability, simple linear regression , and t test . Methods of datacollection was obtained from primary data sourced directly from employees working in BandarLampung Immanuel Hospital on the hospitalization of adult women who are 40 people .From the results, the results of the t test of 3.611 indicates that the variable of work motivation isinfluenced by organizational culture variables .